EFEKTIVITAS MEDIA FLIPBOOK BERBASIS AUGMENTED REALITY DALAM PEMBELAJARAN SAINS SEKOLAH DASAR: SEBUAH TINJAUAN LITERATUR - Yulianti, Nawal; Rahadian, Dian; Suprihadi, Dudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effectiveness of Augmented Reality (AR)-based flipbook media in science learning in elementary schools from cognitive and non-cognitive aspects, as well as to identify opportunities and challenges in its implementation. The method used was a Systematic Literature Review (SLR) of articles published between 2022 and 2025 obtained from Google Scholar, ResearchGate, Semantic Scholar, Garuda, and DOAJ. Of the 228 initial articles, nine articles met the inclusion criteria and were analyzed qualitatively. The results of the study show that AR-based flipbooks are effective in improving students' cognitive learning outcomes with moderate to high N-Gain scores (0.38–0.78) and have a positive impact on students' interest, motivation, and learning engagement. This medium is also considered feasible and practical for use in science education. However, its implementation still faces challenges in the form of device limitations, internet access, teacher readiness, and facility gaps. Overall, Augmented Reality (AR)-based flipbooks have the potential to improve the quality of science education in elementary schools if supported by infrastructure readiness and educator competence.